A36 Neuropathological function of the TANK1-binding kinase 1 (TBK1) in mouse models of Huntington's disease. (12th September 2022) - Raya, Ibrahim; Douahem, Yasmin; Brenner, David; Yilmaz, Rüstem; Cristofani, Riccardo; Poletti, Angelo; Maglione, Vittorio; Weishaupt, Jochen; Parlato, Rosanna
Abstract : Background: Deleterious mutations in the autophagy regulator TANK1-binding kinase 1 (TBK1) cause ALS (Freischmidt A et al., 2015), and at the same time TBK1 overexpression protects against mutant HTT (mHTT) aggregation and toxicity (Hegde RN et al., 2020). The latter aspect most strongly suggests that enhancement of TBK1 expression by (epi-) genetic means could be a potential therapeutic strategy in HD patients. Aims: Here we aim at understanding the kinase-independent role of TBK1 in autophagy and HD progression. Methods/Techniques: Our group has generated Tbk1E696K knock-in mice with a partial loss of TBK1 function and a block in the autophagic flux, while kinase activity is preserved (Brenner et al, unpublished). This model is available to differentiate between kinase activity-dependent and -independent roles of TBK1 for protection against mHTT accumulation and toxicity. Results/Outcome: We generated mutant mice carrying a heterozygous Tbk1E696K knock-in mutation in combination with the expression of mHTT in the zQ175 model. We monitored the accumulation of mHTT intra-nuclear and extra-nuclear inclusions at a pre-symptomatic and early symptomatic stage by immunostaining and image analyses. We found a consistent increase in the number of mHTT inclusions in the double mutant mice. Moreover, we detected alterations of phospho-TBK1 levels in the striatum and cortex of zQ175. Conclusions: Our results suggest that endogenous TBK1 might control disease progression in HD mice due to its function in autophagy. Moreover, this model may be used to identify cellular and molecular changes triggered and shared by mHTT and mTBK1 mice in the early disease stages.